Security For Three-Tiered Web Application - Abdulsalam, Wisal H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Web application protection lies on two levels: the first is the responsibility of the server management, and the second is the responsibility of the programmer of the site (this is the scope of the research).  This research suggests developing a secure web application site based on three-tier architecture (client, server, and database). The security of this system described as follows: using multilevel access by authorization, which means allowing access to pages depending on authorized level; password encrypted using Message Digest Five (MD5) and salt. Secure Socket Layer (SSL) protocol authentication used. Writing PHP code according to set of rules to hide source code to ensure that it cannot be stolen, verification of input before it is sent to database, and update scripts periodically to close gaps in the site. Using 2Checkout company (2CO), which is trusted international electronic money transfer to allow customers pay money in a secure manner.